2021
DOI: 10.1002/acn3.51451
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis comparing first‐line immunosuppressants in neuromyelitis optica

Abstract: Objective As phase III trials have shown interest in innovative but expensive drugs in the treatment of neuromyelitis optica spectrum disorder (NMOSD), data are needed to clarify strategies in the treatment of neuromyelitis optica (NMO). This meta‐analysis compares the efficacy of first‐line strategies using rituximab (RTX), mycophenolate mofetil (MMF), or azathioprine (AZA), which are still widely used. Methods Studies identified by the systematic review of Huang et al. (2019) were selected if they considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Rituximab is a chimeric monoclonal antibody that binds to and depletes CD20-positive B-cells. Its clinical effectiveness in NMOSD has been demonstrated in various retrospective and prospective studies, including AQP4-IgG-positive and -negative (adult and pediatric) patients, with a reduction of attack rates by over 80% [ 52 , 53 , 61 , 74 , 135 , 253 ]. A recent randomized, double-blinded, placebo-controlled trial from Japan (RIN-1) confirmed the efficacy of rituximab in AQP4-IgG-positive NMOSD, although the sample size of the trial was small (Table 2 ) ([ 216 ].…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…Rituximab is a chimeric monoclonal antibody that binds to and depletes CD20-positive B-cells. Its clinical effectiveness in NMOSD has been demonstrated in various retrospective and prospective studies, including AQP4-IgG-positive and -negative (adult and pediatric) patients, with a reduction of attack rates by over 80% [ 52 , 53 , 61 , 74 , 135 , 253 ]. A recent randomized, double-blinded, placebo-controlled trial from Japan (RIN-1) confirmed the efficacy of rituximab in AQP4-IgG-positive NMOSD, although the sample size of the trial was small (Table 2 ) ([ 216 ].…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…AZA was switched-off most often with effectiveness being the main reason for change of therapy. Judging from their respective TSQM scores and literature findings on efficacy and safety, 41 , 42 no definitive conclusion could be drawn yet to explain the dominance of MMF in the study patients. In fact, evidence regarding treatment sequences and switching remains inconclusive.…”
Section: Discussionmentioning
confidence: 92%
“…35 A meta-analysis assessing the relapse rates showed superiority of RTX over MMF but no difference between AZA and MMF in the NMOSD group; however, no difference was seen between the three of them in the AQP4-NMOSD. 36 Given that MMF is a well-established first-line treatment for SLE with major organ manifestations, it may be better suited for the subset of patients with NMOSD who also have SLE. 37 Although improvements were seen in the majority of reviewed, the short follow-up durations make it difficult to accurately assess neurological outcomes, which require long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%